Hitler's courts : betrayal of the rule of law in Nazi Germany - Greene, Joshua, 1950-; Greene, Joshua, 1950- (Stories to Remember, 2006)
When those charged with defending the rule of law betray that trust, the victory of tyrants is assured. Hitler's Courts features archival footage from the Nazi era, rarely seen photographs, and interviews with leading voices in international law. Experts examine the perversion of the courts under Nazi rule and discuss how distinguished lawmakers were capable of complicity in the largest mass murder of men, women and children in history.